Online information and support needs of young people with cancer: a participatory action research study - Lea S; Martins A; Morgan S; Cargill J; Taylor RM; Fern LA (Adolescent Health, Medicine and Therapeutics, 2018)
Sarah Lea,1 Ana Martins,1 Sue Morgan,2 Jamie Cargill,3 Rachel M Taylor,1 Lorna A Fern1 1Cancer Division, University College London Hospitals NHS Foundation Trust, London, UK; 2Teenage Cancer Trust Unit, Leeds Teaching Hospitals NHS Trust, Leeds, UK; 3TYA Cancer Service South West, University Hospitals Bristol NHS Foundation Trust, Bristol, UK Purpose: The Internet is a fully integrated part of young people’s life and it is pivotal that online resources are developed to maximize the potential of the Internet to support those living with and beyond cancer. We sought to understand how young people with a cancer diagnosis use the Internet and to what extent information and support needs are met by existing online resources.Patients and methods: This was a participatory action research study involving 21 young people participating in workshops and individual interviews. Participants aged 13–24 years were diagnosed with a range of cancers. Young people were on treatment or had completed treatment; some had experienced relapse. Workshops consisted of participatory methods including focus group discussions, interactive activities, and individual thought, encompassing online resources used; when, how and what they were searching for, whether resources were helpful and how they could be improved.Results: Young people reported using communication platforms, entertainment sites, social media, medical websites, charity websites, and search engines to find information and support. Different online use and needs were described throughout their cancer timeline and online use was generally driven by negative emotions. Seven factors influenced access and engagement: 1) where young people were on their cancer timeline; 2) external influencing factors, such as family and environments; 3) emotional drivers; 4) what young people search for online; 5) resources, websites, and digital platforms used by young people; 6) availability, accessibility, and assessment of online information and resources; 7) emotional responses to using online resources.Conclusion: The way young people access and engage with online resources is complex with multiple influencing factors including powerful emotional drivers and responses to Internet searching. There is a need to develop resources that support the holistic needs of young people and this should be done in collaboration with young people. Keywords: teenagers, adolescents, young adults, Internet, social media